2020
DOI: 10.1074/jbc.ra119.012233
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of Rab GTPases reveals a role for Rab34 in serum starvation-induced primary ciliogenesis

Abstract: Primary cilia are sensors of chemical and mechanical signals in the extracellular environment. The formation of primary cilia (i.e., ciliogenesis) requires dynamic membrane trafficking events, and several Rab small GTPases, key regulators of membrane trafficking, have recently been reported to participate in ciliogenesis. However, the precise mechanisms of Rab-mediated membrane trafficking during ciliogenesis largely remain unknown. In the present study, we used a collection of siRNAs against 62 human Rabs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
3
16
0
Order By: Relevance
“…A key advance in our study comes from the application of volumetric high-resolution FIB-SEM to reconstruct the membrane structures that form (and fail to form) in RAB34 mutant cells, allowing us to unambiguously determine that cells were arrested at the DAV stage ( G). Our studies also extend recent reports that Rab34 can sometimes localize to cilia (Oguchi et al, 2020;Xu et al, 2018) by defining the precise subset and sub-domains of cilia where Rab34 is found ( Figure 5 A-D). Specifically, the In/Out Assay, 3D-SIM, and expansion microscopy showed that Rab34 is present on the ciliary sheath of nascent intracellular cilia.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A key advance in our study comes from the application of volumetric high-resolution FIB-SEM to reconstruct the membrane structures that form (and fail to form) in RAB34 mutant cells, allowing us to unambiguously determine that cells were arrested at the DAV stage ( G). Our studies also extend recent reports that Rab34 can sometimes localize to cilia (Oguchi et al, 2020;Xu et al, 2018) by defining the precise subset and sub-domains of cilia where Rab34 is found ( Figure 5 A-D). Specifically, the In/Out Assay, 3D-SIM, and expansion microscopy showed that Rab34 is present on the ciliary sheath of nascent intracellular cilia.…”
Section: Discussionsupporting
confidence: 90%
“…However, we found that Rilpl1/2 double-knockout cells neither exhibit ciliogenesis defects nor modulate the Rab34 mutant phenotype (data not shown). Additionally, Rab34 variants that uncouple ciliogenesis from RILP binding have recently been reported (Oguchi et al, 2020). EHD1 is another plausible candidate effector, though we did not detect coimmunoprecipitation of EHD1 with Rab34 (data not shown).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Here, we found that Rab34 is a key mediator of ciliary membrane formation in the intracellular ciliogenesis pathway (Figure 4H). While Rab34 was recently suggested to promote early stages of ciliary membrane formation and to localize to some cilia, 12,13 we now show that Rab34 mediates ciliary vesicle formation and is specifically found on the ciliary sheath of intracellular cilia. Rab34 is also dynamically recruited to the mother centriole during ciliogenesis, and the persistent localization of Rab34-S166N at this site suggests that Rab34 is present on DAVs (Figures 3C-3G).…”
Section: Discussionmentioning
confidence: 49%